Preprocedural planning of transcatheter mitral valve interventions by multidetector CT: What the radiologist needs to know. (2018) - Faggioni, Lorenzo; Gabelloni, Michela; Accogli, Sandra; Angelillis, Marco; Costa, Giulia; Spontoni, Paolo; Petronio, Anna Sonia; Caramella, Davide
Abstract: Mitral regurgitation is the most common valve disorder in the Western world, and although surgery is the established therapeutic gold standard, percutaneous transcatheter mitral interventions are gaining acceptance in selected patients who are inoperable or at an exceedingly high surgical risk. For such patients, multidetector computed tomography (MDCT) can provide a wealth of valuable morphological and functional information in the preoperative setting. Our aim is to give an overview of the MDCT image acquisition protocols, post-processing techniques, and imaging findings with which radiologists should be familiar to convey all relevant information to the Heart Team for successful treatment planning.